Development and validation of an Arabic tool for assessment of post-vaccination confidence in COVID-19 vaccines (ARAB-VAX-CONF) - Rowan Abuyadek; Samar Abd ElHafeez; Mohamed Mostafa Tahoun; Sally Samir Othman; Abdelrahman Omran; Naglaa Fathy; Ramy Mohamed Ghazy (Journal of the Egyptian Public Health Association)
Abstract Background Vaccine confidence is described as a belief that vaccines are effective, safe, and part of a trustworthy health system. The objective of this study was to develop and validate an Arabic tool to evaluate confidence in the received coronavirus disease 2019 (COVID-19) vaccines (ARAB-VAX-CONF). Methods The research team developed the ARAB-VAX-CONF based on three areas specified by the Centers for Disease Control and Prevention (CDC): confidence in vaccine effectiveness, confidence in vaccine safety, and confidence in the healthcare system. The analysis includes data from 406 eligible vaccinated persons (≥ 18 years). Cronbach’s alpha was used to measure internal consistency, while convergent, discriminant, exploratory, and confirmatory factor analyses were used to verify construct validity. Results A total of 406 adults were recruited, with a mean age of 33.0 ± 12.2 years. A total of 63.1% were males, 56.7% were married, 21.9% had chronic conditions, 93.3% were nonsmokers, and 39.6% were obligated to obtain vaccines. The three domains of the scale met the criterion of internal consistency (Cronbach’s alpha > 0.7). Convergent validity was identified by the significant inter-item and item-mean score of the domain correlation (P < 0.001). Discriminant validity was reported as the inter-factor correlation matrix (< 0.7). The Kaiser–Meyer–Olkin sampling adequacy measure was 0.80, and Bartlett’s sphericity test was significant (P < 0.001). Exploratory factor analysis indicated that the scale could be summarized into three factors. Confirmatory factor analysis confirmed the adequate psychometric properties and fit with observed data (root-mean-square error of approximation = 0.08, comparative fit index = 0.945, Tucker-Lewis index = 0.924, standardized root-mean-square residual = 0.086, normed fit index = 0.918, and goodness-of-fit index = 0.909). Conclusions The ARAB-VAX-CONF developed in this study is valid and reliable for assessing confidence in vaccine effectiveness, safety, and confidence in the healthcare system. The ARAB-VAX-CONF can support decision-makers in addressing the gap in vaccine confidence among various populations.